Haribhaktivilāsa of Sanātana Gosvāmin, Volume One Mantras, Initiation and Preparing for Worship (Chapters 1-5). Critical Edition and Annotated Translation - Broo, Måns (Brill, 2023)
Sanātana Gosvāmin's Haribhaktivilāsa (ca. 1540) describes the normative ritual life of a Vaiṣṇava devotee. As it is one of the first Sanskrit texts of Gauḍīya Vaiṣṇava tradition begun by Śrī Kṛṣṇa Caitanya (1486-1533) it presents a fascinating meeting between this ecstatic new religious movement and older, Brahminical tradition. On the basis of eleven manuscripts, this important text has now been for the first time been critically edited. In his extensive introduction, Måns Broo engages with many of the questions that have vexed earlier scholars of this text (such as who really was the author?) by exploring its extensive intertextualities.